Analysis capital budgeting investment projects substation 150 kV for tires company - Andi Setyawan; Hasbullah Hasbullah (Operations Excellence: Journal of Applied Industrial Engineering, 2020)
The electricity consumption continues to increase, including in Indonesia, where the average electricity consumption rises 6.86% per year. In line with the ever-increasing production needs of companies needing more electrical energy during these electrical disturbances often occur due to power shortage. Therefore, the company proposes the investment of the construction of substations 150kv Expected to improve the reliability of electrical energy supply. This research conducted to analyze the value of investment carried by tire companies using historical data and company forecasts using the technical method of economics to analyze its finances. Based on the calculation result with the Payback period (PP) and Discounted Payback Period generates 5.35 years and 6.24 years.  Meanwhile, in the calculation of net present value (NPV) obtained favorable results in the 6th year of Rp 40,944,770,640.32, using an interest rate of 5%. In the calculation of the internal rate of return (IRR), the result of 5.5% concluded that the project return is higher than the minimum attractive rate of return (MARR) of the company by 5.17% of the Bank Indonesia interest rate. Then based on the sensitivity analysis gained that the lower the interest rate on this project, then the faster the return on the investment, and vice versa. The overall analysis of the scenario stated that the investment is worthy of running because it brings profit directly to the company.